Analysis of significant dimensions of e-service quality in Malaysian universities - Al-Nuaimi, I.T.I. (Institute of Electrical and Electronics Engineers Inc., 2016)
The measure of e-service quality in higher education is very critical due to their importance in attracting students and retaining tuition-based returns. The literatures show lack of study on e-SQ in Malaysian universities. This gap should be considered because universities suffer from a continuous rivalry to attract students not only to achieve high income, but also to improve the universities ranking. This research aims to fill this gap by defining the significant dimensions for measuring e-service quality in higher education in Malaysia to help universities to enhance their e-services to exceed their competitors and achieve high tuition-based returns. Nine dimensions are proposed for evaluating e-services in Malaysian universities. These dimensions are selected from the common scales of e-service quality as they can affect the students' perceives and expectations towards the services. Moreover, the selected dimensions are covered all the aspects of e-service quality in higher education in terms of their variation and their contents. A pilot study based on structured questionnaire is conducted with the students of five universities to collect the data necessary for the research. EFA analysis is conducted by using SPSS software package to analyze the data and come out with the new e-SQ dimensions. The results revealed that six dimensions are of great importance in evaluating the e-services provided by the Malaysian universities. Â© 2015 IEEE.